Advanced Aerospace Materials : Aluminum-Based and Composite Structures - Abramovich, Haim (De Gruyter STEM, 2019)
Advanced Aerospace Materials is intended for engineers and students of aerospace, materials, and mechanical engineering. It covers the transition from aluminum to composite materials for aerospace structures and will include essential and advanced analyses used in today's aerospace industries. Various aspects of design, failure and monitoring of structural components will be derived and presented accompanied by relevant formulas and analyses.